2019
DOI: 10.12991/jrp.2019.142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sizes silica nanoparticle on the liver, kidney and brain in rats: Biochemical and histopathological evaluation

Abstract: Silica is among the most popular nanoparticles. Large-scale production and use have increased the risk of human exposure to silica nanoparticles (SiO2NPs). This study aimed to investigate the toxic effects on the kidney, liver and brain of the SiO2NPs. Twenty eight male Wistar albino rats were divided into four groups (n=7 rats) as control (1 mL/day physiological saline administration for 28 day), 6 nm SiO2NP (6 nm, 150 μg/mL/day for 28 day), 20 nm SiO2NP (20 nm, 150 μg/mL/day for 28 day) and 50 nm SiO2NP (50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…A few of these discoveries are consistent with the earlier literature related to the histopathological changes caused by SiO 2 NPs in human liver tissues . Previously, it was recorded that the SiO 2 nanorattles caused histopathological changes in multiple organs of mice including vacuolar degeneration in hepatocytes and the blockage of central vein, indicating that cytoplasmic injury is a type of hydropic degeneration that causes necrosis and degradation of cellular organelles. , …”
Section: Results and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A few of these discoveries are consistent with the earlier literature related to the histopathological changes caused by SiO 2 NPs in human liver tissues . Previously, it was recorded that the SiO 2 nanorattles caused histopathological changes in multiple organs of mice including vacuolar degeneration in hepatocytes and the blockage of central vein, indicating that cytoplasmic injury is a type of hydropic degeneration that causes necrosis and degradation of cellular organelles. , …”
Section: Results and Discussionsupporting
confidence: 86%
“…The production of H 2 O 2 and SOD ion radicals from isolated electron transport chains is a well-known process . The most prevalent ROS is hydrogen peroxide . SiO 2 NPs cause ROS generation and oxidative damage due to unsaturated bonds and a silicon-bounded hydroxyl group on the particle surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Many studies found that SiO 2 NPs are responsible for the toxic adverse effects in different organs as liver, kidney, and brain 6‐8 . Furthermore, different sizes of SiO 2 NPs have an inducible ability to promote oxidative stress and ultrastructural changes in mammalian experimental model 9 . Also, silica NPs exert their cytotoxic effect on both cancer and normal cells mainly through the induction of oxidative damage, apoptosis, and inflammation 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Furthermore, different sizes of SiO 2 NPs have an inducible ability to promote oxidative stress and ultrastructural changes in mammalian experimental model. 9 Also, silica NPs exert their cytotoxic effect on both cancer and normal cells mainly through the induction of oxidative damage, apoptosis, and inflammation. 10 Moreover, in vitro administration of SiO 2 NPs caused notable DNA damage accompanied by activation of the MAPK/ERK1/2 and Nrf2/ARE pathways in colon cancer cells.…”
mentioning
confidence: 99%
“…Hippocampus is a brain component responsible for enabling spatial memory consolidation of information and navigation. When the hippocampus suffers damage, short‐term memory loss, inability to form and retain new memories and disorientation symptoms will be early demonstrated [ 46 ]. The finding of the present behavioural test may suggest that the hippocampus damage was induced by SiO 2 NPs affecting both memory and learning.…”
Section: Resultsmentioning
confidence: 99%